Aspectos epidemiológicos e controle de theileriose equina na região da campanha do Rio Grande do Sul Brasil, 2010 - Torres, Anibal Janczak (2010)
The equine theileriosis, caused by Theileria equi, is an endemic disease of south of Rio Grande do Sul Brazil. There are signs that tick Rhipicephalus boophilus microplus still transmit that disease and in few time, some studies had experimental demonstrated it. The purpose of the first study of this paper was to demonstrate the tick infestation and the role of it in the transmission of the disease. In equines with contact directly with cattle, the serum incidence of the disease was 81,8% and in this group, 31,8% of this horses had tick infestation. In the equines that didn t have contact with cattle, the incidence of the disease was 12% and no tick was found in this horses. The most efficient drug in the treatment of the disease is imidocarb dipropionate. Many studies had demonstrated different doses and protocols of treatment of the disease and the toxicity of it was obvious. No study had show the sterile of T. equi with this drug, but it s a way to treat the acute disease and to control the chronic theileriosis. The acute form of the disease is seemed with fever, icteric and death. The chronic kind of it is seemed with covered coat, hyporexia, low performance in athlete horses and loss of weight. The goal of the second study of this paper was to show the toxicity and the metabolic effects of imidocarb dipropionate drug into two protocols of treatment ( two groups, 2 and 4mg/kg) in serum positive horses to theileriosis. It was seemed through hepatic and renal profile that 2mg/kg of the drug have low toxicity. Horses infected with T. equi keep with the disease for the rest of your lives, and the drug control with imidocarb dipropionate is necessary. The goal of the third study of this paper was to demonstrated, through immunologic test and clinic examination that 2mg/kg of imidocarb dipropionate monthly can control the chronic disease even in stress situations. One group received monthly, through 6 mouths, 2mg/kg of imidocarb dipropionate and the other group, once, in the beginning of it, 4mg/kg. The conclusion of this paper is that the incidence of equine theileriosis have a directly relation with the catle contact because it cause the tick Rhipicephalus Boophilus mircoplus infestation. Mensal dosis with 2mg/kg of imidocarb dipropionate is efficient in the disease control and it had demonstrated that it is not toxic for equine.